Diseño y construcción de una ducha de inducción - Loayza Collaguazo, Oscar Fernando (2017)
The design and construction of the prototype of induction was thought as an idea to replace equipment that uses gas as fuel to generate heat inside the water heating in showers like LPG-based water heaters and electric showers that have a high consumption of electric power. The construction of the induction system was done with the help of electronic elements, power electronics principles and induction fundamentals applied to transformation systems, the principle of model operation is based on creating a magnetic field around a pipe where it will pass Water to the shower. The project was based on a set of methodologies to ensure its operation, three prototypes were made and the third one was selected. The prototype presented all of the necessary parameters for the fulfillment objectives given, which was detailed in the present project. The system consists of two fundamental parts, thus having the control system where a PIC 877A was used in which we proposed the necessary conditions for our prototype to work correctly and a power circuit where a phase control system was applied with Which controls the power that reaches the induction module where the water was heated, obtaining temperatures up to 54 ° C, the working temperature being selected at 35 ° C....